2006
DOI: 10.1111/j.1751-0813.2006.tb13116.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Echinococcus granulosus coproantigens in faeces from naturally infected rural domestic dogs in south eastern Australia

Abstract: Echinococcus granulosus occurs commonly in rural dogs in south eastern Australia and an education program promoting the public health importance of responsible management of rural dogs is urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
(48 reference statements)
0
9
0
1
Order By: Relevance
“…Unlike shelter and household dogs, shepherd dogs seem to be more prone to taeniid infection, which possibly is due to the frequent consumption of raw meat and carcasses [2, 88]. Echinococcosis is still endemic in Greece with a high prevalence reported in livestock [8991].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike shelter and household dogs, shepherd dogs seem to be more prone to taeniid infection, which possibly is due to the frequent consumption of raw meat and carcasses [2, 88]. Echinococcosis is still endemic in Greece with a high prevalence reported in livestock [8991].…”
Section: Discussionmentioning
confidence: 99%
“…6 Absence of this unequivocal indication of infection should not be interpreted as the dogs being uninfected and the test results as false positives. Worm burdens of E. granulosus in Australian domestic dogs are usually low, a few hundred to less than 100 worms.…”
Section: Discussionmentioning
confidence: 97%
“…5 The first and only report of a field study of E. granulosus in Australian dogs using this test collected faeces from rural dogs in two relatively small geographical areas: around Yass in New South Wales (NSW) and the other around Mansfield and Whitfield in Victoria. 6 The authors reported 'an unexpectedly large proportion' of E. granulosus coproantigen-positive dogs (NSW 99/344 (29%), Victoria 37/217 (17.5%)).…”
mentioning
confidence: 99%
“…bu çalışmada köpeklerde %4,02 saptanmıştır. Gerek bu çalışmada köylerde gözlemlendiği, gerekse de benzer amaç-la yapılmış diğer çalışmalarda belirtildiği gibi, köpekler sürü ile beraber gitmediği zamanlarda, haneye ait köpekler birbirlerine yakın ancak birbirlerinin alanlarına geçmelerine imkan vermeyecek uzunlukta zincirle bağlı tutulmaktadır (1,29). Toprak zeminli bu alanlar eski ve yeni dışkı parçalarını içermekte, kancalı kurt ve Trichuris spp.…”
Section: Discussionunclassified